2018
DOI: 10.1002/cssc.201801826
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Size Transparent Wood for Energy‐Saving Building Applications

Abstract: As an energy‐saving building material, transparent wood (TW) is highly attractive because of the advantages of high optical transmittance, excellent mechanical properties, and good thermal insulation. However, the current research is limited to fabricating small‐size samples in the laboratory because thick or large‐size transparent wood is almost impossible to be achieved. A method that can easily and efficiently produce transparent wood with any size and any thickness is desirable for practical applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…To date, the development of green, energy-saving materials has been a prevailing research topic from the perspective of sustainability in response to the rapidly growing burden of energy consumption and environmental pollution 1 , 2 . Natural materials such as wood and its derivatives have been regarded as one of the most important alternatives in green and energy-efficient buildings due to the abundance, renewability, low cost, and sustainability of source materials 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the development of green, energy-saving materials has been a prevailing research topic from the perspective of sustainability in response to the rapidly growing burden of energy consumption and environmental pollution 1 , 2 . Natural materials such as wood and its derivatives have been regarded as one of the most important alternatives in green and energy-efficient buildings due to the abundance, renewability, low cost, and sustainability of source materials 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, transparent wood composites can harvest sunlight effectively due to the light guiding effect, which is meaningful for energy saving and comfortable indoor lighting. With these integrated advantages, the transparent wood composites have emerged as the promising engineering components (e.g., rooftops, windows, and transparent decorations) in green energy-efficient buildings 1,9 .…”
mentioning
confidence: 99%
“…Later, Song et al manufactured the highstrength densified wood by coalescent method which combined NaOH/Na 2 SO 3 solution pretreatment and hot press at 100 °C, exhibiting high specific tensile strength of 422.2 MPa cm 3 g −1 , which is higher than some metals [18]. In recent years, NaOH/Na 2 SO 3 solution system was widely used to degrade hemicellulose and lignin in wood cell walls for preparing transparent wood composites [19], super flexible wood [20] or other functional wood materials [21].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results show that by treating the wood fibers, transparent wood with low thermal conductivity and controllable size can be prepared [13]. Some researchers built a mini-cabin with transparent wood fibers instead of glass and found that the transparent wood fibers had a better thermal insulation effect than glass [14].…”
Section: Introductionmentioning
confidence: 99%